REALIZED GENETIC GAIN AND SEED SOURCE X SITE INTERACTION ON STAND VOLUME PRODUCTIVITY OF ACACIA MANGIUM - Arif Nirsatmanto; Teguh Setyaji; Reny Setyo Wahyuningtyas (Indonesian Journal of Forestry Research, 2014)
Following the results of the comprehensive tree improvement programs for Acacia mangium, it is necessary to estimate the real amount of genetic improvement and to develop an improved seed deployment strategy.  This study was aimed to verify realized genetic gain on stand volume productivity attained by the first-generation Seedling Seed Orchards (SSO) of A. mangium and to identify the magnitude of seed sources x site interaction as a basis for improved seed deployment. Seeds from five SSOs were tested together with seeds from seed stand in genetic gain trials which were established in South Kalimantan and Central Java. Realized gains were calculated from the percentage improvement of respective SSOs compared with seed stand at two and four years of age. Seed source x site interaction was investigated through analysis across the two sites.  Results of the study showed that trees derived from the five SSOs produced better stand volume than those from seed stand. At four years of age, stand volume of the best SSO reached around 127 m3/ha in South Kalimantan and 84 m3/ha in Central Java.  Realized genetic gain were around 66% at two years and 59% at four years in South Kalimantan, and around 136% at two years and 81% at four years in Central Java.  Seed source x site interaction was not significantly different indicating superiority of improved seed were consistent across the two sites with the average realized gain ranging from 18% to 79% and 24% to 62%  at two and four years, respectively. The best three SSOs were SSO-1 located in Pleihari-South Kalimantan, SSO-2 in Pendopo-South Sumatra and SSO-5 in Wonogiri-Central Java, all of which  originated from Papua New Guinea provenances. Improved seed from the orchards could be used at plantation sites without any significant change of the order in their superiority for stand volume productivity.